Exploitation of redox mediators for high-energy-density and high-efficiency lithium-oxygen batteries - Ko, Youngmin (Springer theses., 2021)
This thesis addresses the introduction of redox mediator into lithium-oxygen batteries to improve their electrochemical performance especially in terms of practical energy density and round-trip efficiency. In chapter 1, basic electrochemistry regarding lithium-oxygen batteries and redox mediators are introduced. In chapter 2 to 4, comprehensive researches including the discovery of a new redox mediator inspired by biological system, the investigation on kinetic property of redox mediator, and the prevention of shuttle phenomenon are introduced, followed by chapter 5 summarizing the contents. This thesis is targeted to students and researchers interested in electrochemistry and energy storage systems.